THE USE OF ENGLISH SONG IN TEACHING LISTENING SKILL : A Quasi Experimental of Eleven Grade of Senior High School at SMA Negeri 4 Cimahi - Gusviani, Intan (2014)
This study entitled "The Use of English Song in Teaching Listening Skill (A Quasi Experimental of Eleven Grade of Senior High School at SMA Negeri 4 Cimahi)" is aimed to find out the use of English song as a medium in improving students' listening skill and also investigate the responses given by students' toward the use of English song in teaching listening skill. This study used a quantitative method. Pre-test, post-test and questionnaire were employed to obtain the data. The data gathered through pre-test and post-test were computed using IBM SPSS Statistics 17.0 for Windows while data from questionnaire were analyzed based on the frequency of students' answers and then were calculated and interpreted into percentage. The instrument was a test and analyzed by mean score formula. The result shows that there is a significant difference between the score before treatment and the score after treatments. It can be concluded that the use of songs improved the eleven graders students' listening skill at SMAN 4 Cimahi. The findings from questionnaires showed that the students enjoy the listening learning process using English song. It is indicated from their enthusiasm in finishing the listening test well and their answers to the questionnaires. Thus, the use of English song in teaching listening skill was positively responded by the students. Keywords: Listening Skill, Teaching Listening Skill, Teaching using an English Song. Penelitian ini tentang penggunaan lagu berbahasa Inggris dalam kegiatan mengajarkan kemampuan mendengarkan. Bertujuan untuk mengetahui penggunaan lagu berbahasa Inggris sebagai media dalam meningkatkan keterampilan mendengarkan dan juga mengetahui respon yang diberikan oleh siswa terhadap pemanfaatan lagu berbahasa Inggris dalam kegiatan mengajar keterampilan mendengarkan. Penelitian ini menggunakan metode kuantitatif. Pre-test, post-test dan angket digunakan untuk memperoleh data. Data yang dikumpulkan melalui pre -test dan post-test yang dihitung dengan menggunakan IBM SPSS Statistics 17.0 sedangkan data dari kuesioner dianalisis berdasarkan frekuensi jawaban siswa dan kemudian dihitung dan diinterpretasikan ke dalam persentase. Instrumen penelitiannya adalah tes dan kemudian dianalisis dengan rumus skor rata-rata. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan antara skor sebelum dan skor setelah menggunakan lagu berbahasa inggris. Dengan demikian dapat disimpulkan bahwa penggunaan lagu meningkatkan dapat keterampilan mendengarkan siswa kelas sebelas di SMAN 4 Cimahi. Temuan dari kuesioner menunjukkan bahwa siswa menikmati proses belajar mendengarkan menggunakan lagu berbahasa Inggris. Hal ini diindikasikan dari antusiasme mereka dalam menyelesaikan tes dengan baik dan jawaban mereka terhadap kuesioner. Dengan demikian ,penggunaan lagu berbahasa Inggris dalam keterampilan mendengarkan direspon positif oleh siswa. Kata Kunci: Kemampuan Mendengarkan, Penggunaan Lagu Bahasa Inggris.